Perlindungan Hukum terhadap Anak Korban Eksploitasi Secara Seksual dalam Perspektif Peraturan Perundang-Undangan di Indonesia - Putra, Denny Mahendra (Wajah Hukum, 2024)
The problem of sexual exploitation of children is not just a medical issue, but also involves many aspects, including religion, psychology and law. For this reason, this research was carried out with the aim of knowing and analyzing the regulations for legal protection for child victims of sexual exploitation and policy formulation for legal protection for child victims of sexual exploitation in the future. The research method used is normative juridical with a statutory approach, conceptual approach and case approach. Analysis of legal materials is carried out by interpreting, evaluating and assessing all statutory regulations and relevant legal materials. The results show that the regulation of legal protection for child victims of sexual exploitation is not clearly regulated either in Law Number 13 of 2006 concerning Protection of Witnesses and Victims, Law Number 23 of 2002 concerning Child Protection and Law Number 11 of 2012 Concerning the Juvenile Criminal Justice System and policies for formulating legal protection for child victims of sexual exploitation in the future, namely the need to reform the criminal law regarding provisions that prohibit these acts, both in the draft Criminal Code in the future and the revision of Law Number 13 of 2006, Law Number 23 of 2002 and Law Number 11 of 2012.